Pre Study regarding the use of the circuit method in the Physical Education class for eighth graders - Bogdan Mihaela; Moraru Cristina-Elena (Sport şi Societate)
This study aimed to prove the efficiency of circuit training in the Physical Education class for eighth graders. The study’s objective was to analyse the results obtained in the five force and endurance trials. As for the research subjects, they comprised 63 eighth graders, 36 boys and 27 girls. The tests used were endurance running: 800m girls/1000m boys, trials for the force of the lower limbs: standing long jump and squats, abdominal force: torso raises in 30” and arm force: push-ups in 30”. Findings have provensignificant differences between pre-test and post-tests among boys and girls. From a statistical perspective, bivariate correlations between trials were performed, thus showing that the differences between boys in the pre-test are insignificant. At the same time, in the post-test, all the results are significant, with a P≤0.001. Among girls, the bivariate correlation shows that the results are significant in most trials, in the pre-test, with a P≤0.05, while in the post-test, the results feature in most trials a significance threshold of P≤0.001. Hence, the results highlight that using the circuit method for eighth graders can contribute to the development of the motor qualities of force and endurance.